2015
DOI: 10.1002/adsc.201401026
|View full text |Cite
|
Sign up to set email alerts
|

Formal [3+2] Annulation Involving Allylic Bromides and Thioureas. Synthesis of 2‐Iminothiazolidines through a Base‐Catalyzed Intramolecular anti‐Michael Addition

Abstract: A simple and efficient protocol was developed for the synthesis of 2-iminothiazolidines through a base-mediated [3+2] annulation involving substituted thioureas and allylic bromides bearing electron-withdrawing groups. This domino process consists of nucleophilic displacement, followed by intramolecular anti-Michael addition of the preformed allylic isothiourea under mild conditions to give the thiazolidine core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Among them, Sá et al . have described a base‐mediated [3+2] annulation involving allyl bromide and N‐acylthioureas (Scheme 1a) [4] . Alper et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Sá et al . have described a base‐mediated [3+2] annulation involving allyl bromide and N‐acylthioureas (Scheme 1a) [4] . Alper et al .…”
Section: Methodsmentioning
confidence: 99%
“…Among them, Sá et al have described a base-mediated [3 + 2] annulation involving allyl bromide and N-acylthioureas (Scheme 1a). [4] Alper et al have reported a rhodium-catalyzed synthesis of thiazolidine using carbodiimides (Scheme 1b). [5] But one of the most promising routes is the domino ring-opening cyclization (DROC) of aziridines with isothiocyanates (Scheme 1c).…”
mentioning
confidence: 99%
“…Motivated by these preliminary results with both DBU and NaOH, and being aware that the preparation [18] of substrate 1 a involves a straightforward NaOH-mediated allylation of ethyl acetoacetate (4) with functionalized allylic bromides 5 derived from Morita-Baylis-Hillman adducts, [19,20] we envisioned that the two steps (allylation followed by the deacylative diazo transfer reaction) could be adapted to a one-pot method. Therefore, the α-diazo-γ,δ-unsaturated ester 2 a was readily prepared from allylic bromide 5 a in aqueous alkaline medium, as presented in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…Ferreira and co‐workers have reported a domino reaction for the synthesis of 2‐iminothiazolidines from acylthioureas and allylic bromides bearing electron with‐drawing groups via a base‐mediated [3+2] cycloaddition strategy . Nevertheless, the previous protocols have some inherent limitations such as long reaction time, harsh reaction conditions, tedious work‐up, low yields, etc .…”
Section: Introductionmentioning
confidence: 99%